Cobalt-Based Metal-Organic Frameworks and Their Derivatives for Hydrogen Evolution Reaction - Han, Wenjuan; Li, Minhan; Ma, Yuanyuan; Yang, Jianping (Frontiers in Chemistry, 2020)
Hydrogen has been considered as a promising alternative energy to replace fossil fuels. Electrochemical water splitting, as a green and renewable way for hydrogen production, has been drawing more and more attention. In order to improve hydrogen production efficiency and lower energy consumption, efficient catalysts are required to drive the hydrogen evolution reaction (HER). Cobalt (Co)-based metal-organic frameworks (MOFs) are porous materials with tunable structure, adjustable pores and large specific surface areas, which has attracted great attention in the field of electrocatalysis. In this review, we focus on the recent progress in Co-based metal-organic frameworks and their derivatives, including their compositions, morphologies, architectures and electrochemical performances. The challenges and development prospects related to Co-based metal-organic frameworks as HER electrocatalysts are also discussed, which might provide some insight in electrochemical water splitting for future development.